Holistic Integrative ECD Partnership at Al Ghazali Early Childhood Center - Kurnia, Sari; Ahmad, Suriansyah; Novitawati, Novitawati (Journal of English Language and Education, 2025)
The success of the implementation of PAUD HI cannot be achieved by one party alone. Partnerships with various parties, such as parents, the community, and  other stakeholders Partnerships are the key to success in the development of Integrative Holistic Early Childhood Education. The purpose of this study is to describe the partnership carried out by PAUD Al-Ghazali so that the realization of Integrative Holistic PAUD (HI). This research is a descriptive qualitative research. The data was obtained using interview data collection techniques, observations, and documentation. Based on the results  of the research Through close partnerships with parents, related agencies, higher education institutions, and protection and health institutions, PAUD Al Ghazali has succeeded in providing education, health, nurturing, nutrition, and protection services that support and complement each other..